Pelanggaran Hak Merek Yang Memiliki Persamaan Pada Pokoknya (Studi Kasus Sengketa Merek ‘GOTO’ antara Gojek dan Tokopedia Dengan PT Terbit Financial Technology) - Marchelina Ramadhanty Wahyu Utami; Siti Hapsah Isfardiyana (Fakultas Hukum Universitas Islam Indonesia, 2023)
A brand is a symbol in the form of two dimensions and/or dimensions to differentiate between goods and/or services produced by individuals or legal entities with goods and/or services belonging to three. The purpose of the protection of trademark rights is to provide exclusive rights for the holder so that the mark is not used by other business actors. Mark Rights are regulated in Law Number 20 of 2016 concerning Marks and Geographical Indications. Trademark rights are constitutive rights, which means that whoever registers first gets the right. Trademark rights are exclusive rights, so their ownership must be protected. Violation of trademark rights if the mark has similarities in principle with the registered mark. As happened in the case of Gojek and Tokopedia against PT Terbit Financial Technology related to the “GOTO” brand. Article 83 paragraph (1) of Law Number 20 of 2016 stipulates that parties who feel aggrieved because of a mark that makes their mark can file a claim for compensation and/or temporary suspension to prevent greater losses.